Cdc42/Rac Interactive Binding Containing Effector Proteins in Unicellular Protozoans With Reference to Human Host: Locks of the Rho Signaling - Umarao, Preeti; Rath, Pragyan Parimita; Gourinath, Samudrala (Frontiers in Genetics, 2022)
Small GTPases are the key to actin cytoskeleton signaling, which opens the lock of effector proteins to forward the signal downstream in several cellular pathways. Actin cytoskeleton assembly is associated with cell polarity, adhesion, movement and other functions in eukaryotic cells. Rho proteins, specifically Cdc42 and Rac, are the primary regulators of actin cytoskeleton dynamics in higher and lower eukaryotes. Effector proteins, present in an inactive state gets activated after binding to the GTP bound Cdc42/Rac to relay a signal downstream. Cdc42/Rac interactive binding (CRIB) motif is an essential conserved sequence found in effector proteins to interact with Cdc42 or Rac. A diverse range of Cdc42/Rac and their effector proteins have evolved from lower to higher eukaryotes. The present study has identified and further classified CRIB containing effector proteins in lower eukaryotes, focusing on parasitic protozoans causing neglected tropical diseases and taking human proteins as a reference point to the highest evolved organism in the evolutionary trait. Lower eukaryotes’ CRIB containing proteins fall into conventional effector molecules, PAKs (p21 activated kinase), WASPs (Wiskoit-Aldrich Syndrome proteins) family, and some have unique domain combinations unlike any known proteins. We also highlight the correlation between the effector protein isoforms and their selective specificity for Cdc42 or Rac proteins during evolution. Here, we report CRIB containing effector proteins; ten in Dictyostelium and Entamoeba, fourteen in Acanthamoeba, one in Trypanosoma and Giardia. CRIB containing effector proteins that have been studied so far in humans are potential candidates for drug targets in cancer, neurological disorders, and others. Conventional CRIB containing proteins from protozoan parasites remain largely elusive and our data provides their identification and classification for further in-depth functional validations. The tropical diseases caused by protozoan parasites lack combinatorial drug targets as effective paradigms. Targeting signaling mechanisms operative in these pathogens can provide greater molecules in combatting their infections.